The position of the Arab Gulf states on the British withdrawal from the area east of the Suez Canal for the period 1968-1971 (Journal of the College of Basic Education, 2022)
After the decline of British influence in the Arab Gulf region and the Levant in general, the British empire that does not set the sun on its colonies and the emergence of national movements led by the Arab tribes, the American-Iranian harmony appeared to the public, especially during the time of the Shah of Iran, Muhammad Reza Pahlavi (1941-1978) due to the importance of the region in terms of its location The geographic link that connects the East with the West, so Iran hastened to occupy the three Arab islands (Greater Tunb, Lesser Tunb, and Abu Musa) on November 30, 1971, one day before the collapse of the British protectorate, to fill the void that occurs as a result of the British withdrawal from the region and control of this outlet.